The religious poetry of the portuguese-brazilian new christian João Mendes da Silva - Topa, Francisco (2019)
This essay aims to present and to study the religious poetry (partially unpublished) of the New Christian born in Rio de Janeiro João Mendes da Silva (1659-1736), father of the playwright António José. After a brief summary of his biography, I introduce his profane literary work and then the religious one. Despite its not so good quality, this poetry is a valid cultural testimony (literary and Catholic) and represents a sad page of the Portuguese-Brazilian history that cannot be ignored.